Paediatric practice: an approach to a child with fever - Sharma, P.R.; Bhattarai, P.; Sharma, M. (Journal of Institute of Medicine Nepal, 2007)
Nearly seventy percent of all children between the ages of one week and two-years-of-age are brought to Kanti Children’s Hospital for some Type of febrile episode. And 50%of these visits are for temperatures greater than or equal to 39 degrees celsius. These children may have significant bacterial infection. In 35%of these children there’s no definable source for the fever on clinical examination. So the child that don’t have identifiable sources could be either bacteremic, meningitis or could have a bone or joint infection in evolution. Simple clinical observation to differentiate a well looking infant from a toxic infant helps to differentiate children who need admisson or out patient follow-up. Journal of Institute of Medicine Vol.27(3) 2005